2020
DOI: 10.1007/s13313-020-00694-9
|View full text |Cite|
|
Sign up to set email alerts
|

Chasing myrtle rust in New Zealand: host range and distribution over the first year after invasion

Abstract: After the detection of the myrtle rust pathogen, Austropuccinia psidii, in New Zealand, a biosecurity response was initiated, including a widespread surveillance programme. Through an intensive public awareness initiative, the general public was highly engaged in reporting myrtle rust infections and added significant value to the surveys by reporting first detections from most of the areas that are now known to be infected. During the first year of the response, Austropuccinia psidii was found in areas that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…We found L. bullata and M. excelsa share similar climate (precipitation/temperature) tolerances to the disease (Figure 5; Appendix ) and therefore have limited refugia, even under the less‐extensive Scenario 1 (Figure 4a; Appendix ). Other species with limited refugia (<30% of their range) include M. albiflora , M. robusta and S. maire , but observed infection of these species to date is low (Toome‐Heller et al., 2020). Lophomyrtus obcordata has a greater tolerance of cooler temperatures, resulting in a larger proportion of its habitat acting as refugia (Figure 4c), which could be an in situ conservation tool for this species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found L. bullata and M. excelsa share similar climate (precipitation/temperature) tolerances to the disease (Figure 5; Appendix ) and therefore have limited refugia, even under the less‐extensive Scenario 1 (Figure 4a; Appendix ). Other species with limited refugia (<30% of their range) include M. albiflora , M. robusta and S. maire , but observed infection of these species to date is low (Toome‐Heller et al., 2020). Lophomyrtus obcordata has a greater tolerance of cooler temperatures, resulting in a larger proportion of its habitat acting as refugia (Figure 4c), which could be an in situ conservation tool for this species.…”
Section: Discussionmentioning
confidence: 99%
“…During surveillance immediately following the outbreak, myrtle rust was detected most frequently on L. bullata, L. obcordata and their hybrid, and also on M. excelsa (Toome-Heller et al, 2020); and a recent study found these species have little resistance across genotypes (Smith et al, 2020). We found L. bullata and M. excelsa share similar climate (precipitation/temperature) tolerances to the disease ( Figure 5; Appendix S9) and therefore have limited refugia, even under the less-extensive Scenario 1 (Figure 4a; Appendix S8).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Austropuccinia psidii is native to South America (Coutinho et al 1998) but multiple strains of this pathogen have spread worldwide during the last few decades (Stewart et al 2017) and it is now regarded as a globally invasive pathogen threatening native Myrtaceae, Myrtaceae-related economies, and ecosystems (Pegg et al 2017). The pandemic biotype (Stewart et al 2017) of A. psidii was first detected on mainland Aotearoa (New Zealand) in May 2017 in Kerikeri (du Plessis et al 2019; Guy & Barry 2017) but was rapidly found in other regions across Te Ika a Māui (North Island) (Beresford et al 2018;Toome-Heller et al 2020).…”
Section: Introductionmentioning
confidence: 99%